Neuropeptide Y (NPY) in cerebrospinal fluid from patients with Huntington's Disease: increased NPY levels and differential degradation of the NPY1-30 fragment - Wagner, Leona; Bjorkqvist, Maria; Lundh, Sofia Hult; Wolf, Raik; Boergel, Arne; Schlenzig, Dagmar; Ludwig, Hans-Henning; Rahfeld, Jens-Ulrich; Leavitt, Blair; Dernuth, Hans-Ulrich; Petersen, Asa; von Hörsten, Stephan (Journal of Neurochemistry, 2016)
Huntington's disease (HD) is an inherited and fatal polyglutamine neurodegenerative disorder caused by an expansion of the CAG triplet repeat coding region within the HD gene. Progressive dysfunction and loss of striatal GABAergic medium spiny neurons (MSNs) may account for some of the characteristic symptoms in HD patients. Interestingly, in HD, MSNs expressing neuropeptide Y (NPY) are spared and their numbers is even up-regulated in HD patients. Consistent with this, we report here on increased immuno-linked NPY (IL-NPY) levels in human cerebrospinal fluid (hCSF) from HD patients (Control n = 10; early HD n = 9; mid HD n = 11). As this antibody-based detection of NPY may provide false positive differences as a result of the antibody-based detections of only fragments of NPY, the initial finding was validated by investigating the proteolytic stability of NPY in hCSF using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS) and selective inhibitors. A comparison between resulting NPY-fragments and detailed epitope analysis verified significant differences in IL-NPY1-36/3-36 and NPY1-30 levels between HD patients and control subjects with no significant differences between early vs mid HD cases. Ex vivo degradomics analysis demonstrated that NPY is initially degraded to NPY1-30 by cathepsin D in both HD patients and control subjects. Yet, NPY1-30 is then further differentially hydrolyzed by thimet oligopeptidase (TOP) in HD patients and by neprilysin (NEP) in control subjects. Furthermore, altered hCSF TOP-inhibitor Dynorphin A1-13 (Dyn-A1-13 ) and TOP-substrate Dyn-A1-8 levels indicate an impaired Dyn-A-TOP network in HD patients. Thus, we conclude that elevated IL-NPY-levels in conjunction with TOP-/NEP-activity/protein as well as Dyn-A1-13 -peptide levels may serve as a potential biomarker in human CSF of HD. Huntington's disease (HD) patients' cerebrospinal fluid (CSF) exhibits higher neuropeptide Y (NPY) levels. Further degradomics studies show that CSF-NPY is initially degraded to NPY1-30 by Cathepsin D. The NPY1-30 fragment is then differentially degraded in HD vs control involving Neprilysin (NEP), Thimet Oligopeptidase (TOP), and TOP-Dynorphin-A network. Together, these findings may help in search for HD biomarkers.
EVALuna2:24983